Sistema de conservação preventiva: acondicionamento de documentos gráficos - Rosa, Clarissa Andreola da (2011)
This Project develops a preventive conservational option to the Department of Historical Documentation of the “Universidade Tecnológica Federal do Paraná”, through the creation of packing to shelter the documents of the department collection. The project is driven especially by the packing of the Ata Book regarding the installation of the “Escola Federal de Aprendizes Artifices do Paraná” dated from 1910 and printed papers stored by the institution dated from 1955 until latest editions. The project studies the collection portrait, the materials in it, and the collection physical and financial structures. It also made a detailed study of the characteristics of each piece to be packed, such as, material and conservational status, identifying the needs regarding the packaging and the main degradation agents in action. It identifies the materials at hand in the national market, which are suitable to the project, needs, fulfilling standards required to the production of conservational casings. It also grants an identifying system to the packages, regarding the casing subjected collection pieces.